La Pandemia ed i suoi con-testi (Società e diritti, 2021)
AbstractThe analysis of the distance between social practices and law often forgets how this relationship must necessarily include the context, the physical, natural and human environment, where this relationship takes place: the conditioning posed by the physical, natural and human environment represent and they constitute as many factors capable of conditioning socio-juridical action, therefore the subjects, the law and the context in which such action takes place. These are aspects with respect to which politics, law but also the social context often pursue the problems posed by the pandemic society in continuous and rapid transformation. It is therefore necessary to analyze the legal implications of the "new social problems" connected to development, the spread of the global pandemic from Covid-19 or the consequences produced by "brutal facts", physical, natural and human, on socio-legal action, on politics , on the law and on the social context